PERENCANAAN KOLABORASI DALAM PENGELOLAAN SAMPAH SEBAGAI UPAYA PEMBANGUNAN LINGKUNGAN YANG BERKELANJUTAN - Ely Sufianti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Coolaborative Planning is planning practice co-existing with collaborative governance in public administrative perspective. Inclusiveness and participation of stakeholders are important aspects. Stakeholders do authentic dialogue which results in consensus. This activity is initiated bu the government. Consensus then is implemented by all stakeholders for achieving the main goal. The steps of collaborative planning for waste management are deciding when to collaborate, setting up a successful process, determining who will participate, organizing the process, creating a decision-making structure, helping participants work together, sharing information, and implementing agreements.